2019
DOI: 10.1038/s41598-019-49229-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SMG7 14-3-3-like domain reveals phosphoserine binding-independent regulation of p53 and UPF1

Abstract: The 14-3-3-related protein SMG7 plays critical roles in regulation of DNA damage response and nonsense-mediated mRNA decay (NMD). Like 14-3-3, SMG7 engages phosphoserine-dependent protein interactions; however, the precise role of phosphorylation-mediated SMG7 binding remains unknown. Here, we show that DNA damage-induced SMG7-p53 binding requires phosphorylated Ser15 on p53, and that substitution of the conserved lysine residue K66 in the SMG7 14-3-3-like domain with the glutamic acid (E) abolishes interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Following treatment, we conducted western blotting using an anti‐puromycin antibody, as well as total Nedd4‐2 and phosphorylated Nedd4‐2 at serine‐342 and serine‐448 in order to validate the mutations as well as the specificity of the mutations to serine‐342 (Figure 5a). The mutations were additionally validated through sequencing because our phospho‐specific antibody did not recognize our phospho‐mimetic protein, likely due the change in the amino acid sequence (Cowen et al., 2019). As expected, the mock transfected HEK cells showed a dramatic decrease in puromycin incorporation following Tg treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Following treatment, we conducted western blotting using an anti‐puromycin antibody, as well as total Nedd4‐2 and phosphorylated Nedd4‐2 at serine‐342 and serine‐448 in order to validate the mutations as well as the specificity of the mutations to serine‐342 (Figure 5a). The mutations were additionally validated through sequencing because our phospho‐specific antibody did not recognize our phospho‐mimetic protein, likely due the change in the amino acid sequence (Cowen et al., 2019). As expected, the mock transfected HEK cells showed a dramatic decrease in puromycin incorporation following Tg treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The splicing factor SRSF3 was shown to inhibit alternative splicing of the p53β-unique exon, identifying another negative regulator of p53β expression [ 15 ]. Moreover, the splicing factor SRSF1 was also identified as an additional negative regulator of p53β expression, as p53β levels increased upon SRSF1 inhibition or knockdown [ 16 , 17 ]. Finally, while alternative splicing is responsible for the expression of p53β, the act of incorporating the p53β-unique exon introduces a premature termination codon (PTC), which is typically recognized by nonsense-mediated RNA decay (NMD) machinery [ 18 ].…”
Section: Post-transcriptional Regulation Of P53βmentioning
confidence: 99%
“…Finally, while alternative splicing is responsible for the expression of p53β, the act of incorporating the p53β-unique exon introduces a premature termination codon (PTC), which is typically recognized by nonsense-mediated RNA decay (NMD) machinery [ 18 ]. Consequently, the NMD factors UPF1 and SMG7 have been shown to increase p53β expression [ 17 ], which indicates that p53β could be a target for NMD. The balance between alternative splicing and NMD of p53β remains to be elucidated, especially in the presence of cellular stressors.…”
Section: Post-transcriptional Regulation Of P53βmentioning
confidence: 99%
“…DNA damage enhances the binding of SMG7-p53, which requires Ser15 phosphorylation of p53. In addition, mutation of K66M in SMG7 blocks the binding of p53 and UPF1 [ 30 ]. It has been reported that SMG7 has an important role in the p53-mediated response to genotoxic stress by regulating p53 stability, and SMG7 physically interacts with MDM2 [ 31 ].…”
Section: Resultsmentioning
confidence: 99%